Biological Weighting Function for the Mortality of Boeckella gracilipes (Copepoda, Crustacea) Derived from Experiments with Natural Solar Radiation - Tartarotti, Barbara (2000)
We performed in situ experiments during the austral summer of 1998 to quantify the mortality of the freshwater copepod Boeckella gracilipes as a function of the UV dose. The copepods were exposed to solar radiation at the water‐surface for ∼24–34 h. Long‐pass cut‐off filters (Schott) were used in the exposure experiments. UV radiation and PAR were measured with an IL‐1700 (International Light Inc.) and a PUV‐500 radiometer (Biospherical Instruments Inc.). A biological weighting function for UV‐induced mortality was calculated by fitting a model based on a logistic curve. Our results show that UV damage in this species is strongly wavelength‐ and dose‐dependent. B. gracilipes was highly vulnerable to both UV‐B (290–320 nm) and UV‐A radiation (< 360 nm). The shape of the BWF obtained for B. gracilipes resembles more closely the action spectra (AS) † for UV‐induced erythema, than the AS for naked DNA.